Synergistic effects of physical-mental mixed fatigue on badminton forehand smash performance - Bing Wang; Lan Ding; Meng Liu; Yan Huang; Jun Ai (PLoS ONE, 2026)
Purpose Badminton’s forehand jump smash is critical for offensive success, yet its performance often declines under fatigue. Previous studies have separately examined physical or mental fatigue, neglecting their combined impact, common in competitive scenarios. This study investigates the synergistic effects of physical-mental mixed fatigue on smash performance, focusing on speed and accuracy in badminton athletes using a dual-channel neuromuscular-mental fatigue model. Method Twenty-four national-level 1 badminton athletes participated. A fatigue protocol combining vertical jumps, sprints, and randomized target-hitting tasks induced simultaneous physical and mental fatigue. Athletes executed 10 smashes at baseline and after mild, moderate, and severe fatigue. Smash speed was measured by radar, and accuracy was scored via a camera-based system. Fatigue levels were assessed with RPE and VAFS scales, analyzed through repeated-measures ANOVA and linear mixed-effects models. Results Increased fatigue significantly reduced smash speed by 10.6% and accuracy by 46.1% from baseline to severe fatigue conditions (both p < 0.001). Under moderate-to-severe fatigue, a significant negative correlation between smash speed and accuracy emerged (moderate fatigue r = −0.58, severe fatigue r = −0.53, both p < 0.01), indicating a notable speed-accuracy trade-off. Discussion Physical-mental mixed fatigue significantly impairs badminton smash performance, particularly accuracy. The observed speed-accuracy trade-off highlights challenges in maintaining technical quality under fatigue. Future research should explore broader athlete populations and integrate neurophysiological measures, informing strategies for cognitive-physical training and fatigue management in elite badminton athletes. These findings suggest that coaches should integrate fatigue simulation and mitigation strategies into technical training to sustain performance under competitive conditions.